Blood pressure and neuropsychological test performance in healthy postmenopausal women. (June 2016) - Alsumali, Adnan; Mekary, Rania A.; Seeger, John; Regestein, Quentin
Highlights: Various effects of increased diastolic blood pressure on neuropsychological test performance are proposed. Increased diastolic blood pressure was associated with an increase in the time needed to perform 'selective attention'. An increase in diastolic blood pressure was associated with a decrease in neuropsychological test performance among healthy postmenopausal women experiencing hot flashes. Abstract: Purpose: To study the association between blood pressure and neuropsychological test performance in healthy postmenopausal women. Methods: Data from 88 healthy postmenopausal women aged 46–73 years, who were not experiencing hot flashes, and who had participated in a prior drug trial, were analyzed to find whether baseline blood pressure was associated with impaired performance on neuropsychological testing done at 3 follow-up visits separated by 4 weeks. Factor analysis was used to reduce the dimensions of neuropsychological test performance. Mixed linear modeling was used to evaluate the association between baseline blood pressure and repeatedly measured neuropsychological test performance at follow-up in a complete case analysis (n = 53). In a sensitivity analysis (n = 88), multiple-imputation using the Markov Chain Monte Carlo method was used to account for missing data (blood pressure results) for some visits. Results: The variables recording neuropsychological test performance were reduced to two main factors (Factor 1 = selective attention; Factor 2 = complex processing). In the complete case analysis, the association between a 20-mmHg increase in diastolic blood pressure and Factor 1 remained statistically significant after adjusting for potential confounders, before adjusting for systolic blood pressure (slope = 0.60; 95%CI = 0.04, 1.16), and after adjusting for systolic blood pressure (slope = 0.76; 95%CI = 0.06, 1.47). The positive slopes indicated an increase in the time spent performing a given task (i.e., a decrease in neuropsychological test performance). No other significant associations were found between systolic blood pressure and either factor. The results did not materially change after applying the multiple-imputation method. Conclusions: An increase in diastolic blood pressure was associated with a decrease in neuropsychological test performance among older healthy postmenopausal women experiencing hot flashes.